High-resolution ALMA observations of H2S in LIRGs: Dense gas and shocks in outflows and circumnuclear disks - Sato, Mamiko T.; Aalto, S.; König, Sabine; Kohno, Kotaro; Viti, Serena; Gorski, Mark; Combes, Francoise; Garcia-Burillo, Santiago; Harada, Nanase; van der Werf; Paul; Otter, Justin; et al. (EDP Sciences, 2026)
Context
Molecular gas plays a critical role in regulating star formation and nuclear activity in galaxies. Sulphur-bearing molecules, such as H2S, are sensitive to the physical and chemical environments in which they reside and are potential tracers of shocked, dense gas in galactic outflows and active galactic nuclei (AGNs).
Aims. We aim to investigate the origin of H2S emission and its relation to dense gas and outflow activity in the central regions of nearby infrared-luminous galaxies.
Methods
We present Atacama Large Millimeter/submillimeter Array (ALMA) Band 5 observations of the ortho-H2S 11, 0 − 10, 1 transition in three nearby galaxies: NGC 1377, NGC 4418, and NGC 1266. We performed radiative transfer modelling using RADEX to constrain the physical conditions of the H2S-emitting gas and compare the results to ancillary CO and continuum data.
Results
We detect compact H2S emission in all three galaxies, arising from regions smaller than ∼150 pc. The H2S spectral profiles exhibit broad line wings, suggesting an association with outflowing or shocked gas. In NGC 4418, H2S also appears to be tracing gas that is counter-rotating. A peculiar redshifted emission feature may be inflowing gas, or possibly a slanted outflow. RADEX modelling indicates that the H2S-emitting gas has high densities (nH2 ≳ 107 cm−3) and moderately warm temperatures (40−200 K). The derived densities exceed those inferred from CO observations, implying that H2S traces denser regions of the ISM.